Processo decisório no Governo do Estado do Ceará (1995-1998): o porto e a refinaria - Aquino, Jakson Alves de (2000)
The dissertation researched policy decision making process in the State Government of Ceará following the downfall of the "coronels", the traditional power elite that governed during the military regime. The decision to construct a refinery (Refinaria do Nordeste — Renor) and a harbor located within the industrial district of Pecém (Complexo Industrial e Portuário do Pecém — CIPP) were used as case studies to interpret the process. The public works of the CIPP were financed at large by the Federal Government and Renor, located in CIPP, will be built by private capital. In spite of that, in both cases it has been decisive the participation of the State Government during Governor Tasso Jereissati's second mandate (1995-98) in determining that outcome. The review of the literature on decision making process revealed a polarization between a pluralist version of power, which defends the idea that voters' interests are represented by political decisions makers, and an elitist conception, which argues that a dominant elite centralizes the power of decision. The research mapped the power structure within the State Government of Ceará and investigated the origin of ideas that led to the construction of CIPP and to the search for private investments for the construction of the refinery. The purpose was to trace changes in the ideas on development that guided the decision making process. The Government of Ceará expected that the infrastructure of CIPP, together with the refinery and a steel plant, already under construction, will increase the State attractiveness of petrochemical and metal-mechanic clusters, thus enlarging and diversifying exports and increasing the participation of Ceará in Brazilian GDP. Interviews with leading policy makers, analysis of official documents and newspapers composed the bulk of the data used in the thesis.